2002
DOI: 10.1002/cncr.10919
|View full text |Cite
|
Sign up to set email alerts
|

An interinstitutional and interspecialty comparison of treatment outcome data for patients with prostate carcinoma based on predefined prognostic categories and minimum follow‐up

Abstract: BACKGROUND The optimal management of patients with clinically localized prostate carcinoma remains undefined due in part to the absence of well‐designed, prospective, randomized trials. The current study was conducted to compare and contrast outcomes with different forms of therapy for patients with prostate carcinoma who were treated at several institutions using predefined prognostic categories. METHODS A retrospective study of 6877 men with prostate carcinoma who were treated between 1989 and 1998 at 7 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 34 publications
0
29
0
2
Order By: Relevance
“…A recent prospective study of over 6500 patients treated with either brachytherapy, radiotherapy or radical prostatectomy, who were stratified according to a PSA and Gleason score, would appear to show that there is no significant difference between any of the primary treatment options. 34 The only consistent finding was that conformal beam radiotherapy fared better than conventional external beam radiotherapy but no individual treatment had overall superiority. A further retrospective comparison of 1305 patients treated for stage T1-2 prostate cancer by either radical prostatectomy or brachytherapy failed to demonstrate any clear superiority of one treatment over the other.…”
Section: Comparison Resultsmentioning
confidence: 99%
“…A recent prospective study of over 6500 patients treated with either brachytherapy, radiotherapy or radical prostatectomy, who were stratified according to a PSA and Gleason score, would appear to show that there is no significant difference between any of the primary treatment options. 34 The only consistent finding was that conformal beam radiotherapy fared better than conventional external beam radiotherapy but no individual treatment had overall superiority. A further retrospective comparison of 1305 patients treated for stage T1-2 prostate cancer by either radical prostatectomy or brachytherapy failed to demonstrate any clear superiority of one treatment over the other.…”
Section: Comparison Resultsmentioning
confidence: 99%
“…Potters and colleagues found that the 7-year bRFS hazard ratio for radiotherapy (all treated with ≥70 Gy) compared to surgery was 1.18 (0.86-1.62), 22 while Martinez and colleagues found no difference in the 7-year bRFS odds ratio: 0.98 (0.55-1.74) with radiotherapy doses between 59-70 Gy. 23 Vicini and colleagues found no statistically significant differences in bRFS for any subgroup formed and varying approaches to radiotherapy delivery across seven institutions; 24 and Kupelian and colleagues computed a hazard ratio of 1.01 (p = 0.96) comparing radiotherapy (68-78 Gy) to surgery for difference in bRFS after control for disease severity and other key confounding variables. 25 D'Amico and colleagues found no difference in 8-year bRFS for intermediate-risk patients with high volume tumours and high-risk patients, however they did observe higher 8-year bRFS for low-risk patients or intermediate-risk patients with low volume tumours treated surgically compared to the radiotherapy group whose median dose was 66 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…LDR brachytherapy S Voulgaris et al prostate cancer. 5,6,21 Contemporary patients tend to place equal emphasis on the expected prostate cancer survival outcomes and post-treatment quality of life associated with each treatment modality. 33 Therefore issues concerning quality of life after treatment for localized prostate cancer are becoming increasingly important.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Available evidence from non-randomized cohort studies suggest that all modalities have comparable results, in terms of cancer control and survival. [4][5][6] As a result, patients with localized prostate cancer are often faced with the dilemma of choosing a treatment based on the side-effect profile and the potential impact on the quality of life.…”
Section: Introductionmentioning
confidence: 99%